Jan van der Noordaa (1934–2015); A Virologist Pur Sang - Ben Berkhout; Michael Bukrinsky (Viruses, 2015)
Our loyal friend and colleague, Jan van der Noordaa, passed away unexpectedly at the age of 80 on the evening of 17 June 2015. [...]